2021
DOI: 10.1093/rpd/ncab096
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Annual Effective Dose Due to Inhalation and Ingestion of Radon From Groundwater at the Southeast Coastal Area, Bangladesh

Abstract: Naturally occurring radon-222 was evaluated for its use in estimating annual effective dose exposure in groundwater samples of the southeast coastal area of Bangladesh. On-site radon concentration was measured in groundwater using AlphaGUARD PQ2000 PRO (Saphymo, Germany) radon monitor. The measured values range 0.36–15.70 Bq per l, which lies within the safe limit of 4–40 Bq per l recommended by UNSCEAR. On the contrary, few samples show radon concentration above the safe limit of 11.1 Bq per l recommended by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In their work, they found out the level of uranium-238 in one sample to have a mean of 213.97 ± 1.3 Bq/kg, which was way higher than the world average value of 35 Bq/kg [69] and higher than the uranium-238 levels reported in the literature in Kuwait and Oman [70][71][72]. Moreover, the investigative work conducted by Deeba on radon in groundwater in Bangladesh also attributed the presence of radon in groundwater to the existence of radium in soil and bedrock around the aquifer [47]. This finding can be supported by the study conducted in Qatar, which reported a radium-226-equivalent level of 228.2 ± 9.4 in Qatar [54,55].…”
Section: Radon Measurementsmentioning
confidence: 63%
“…In their work, they found out the level of uranium-238 in one sample to have a mean of 213.97 ± 1.3 Bq/kg, which was way higher than the world average value of 35 Bq/kg [69] and higher than the uranium-238 levels reported in the literature in Kuwait and Oman [70][71][72]. Moreover, the investigative work conducted by Deeba on radon in groundwater in Bangladesh also attributed the presence of radon in groundwater to the existence of radium in soil and bedrock around the aquifer [47]. This finding can be supported by the study conducted in Qatar, which reported a radium-226-equivalent level of 228.2 ± 9.4 in Qatar [54,55].…”
Section: Radon Measurementsmentioning
confidence: 63%
“…1 shows that radon concentration results were ranging from 1.04 to 21.87 Bq/L with an average of 8.26±3.77 Bq/L. The results of radon content measured from 32 groundwater samples were below the action level of 11.1 Bq/L, as advised by US EPA [1,21], on the other hand, 11 groundwater samples were more than the action level. Calculation of the annual effective dose from the results of radon concentration is detailed as follows: Dinh were ranging from 2.6 to 54.69 µSv/y with an average of 20.7±9.4 µSv/y, and Ding were ranging from 0.19 to 3.94 µSv/y with an average of 1.5±0.7 µSv/y.…”
Section: Resultsmentioning
confidence: 82%
“…Calculation of the annual effective dose from the results of radon concentration is detailed as follows: Dinh were ranging from 2.6 to 54.69 µSv/y with an average of 20.7±9.4 µSv/y, and Ding were ranging from 0.19 to 3.94 µSv/y with an average of 1.5±0.7 µSv/y. Dtotal (Dinh+Ding) were ranging from 2.8 to 58.62 µSv/y with an average of 22.2±10.1 µSv/y, Dtotal for the inhaled and ingested radon concentrations from groundwater for people in the mentioned locations is less than that introduced by WHO is 100 μSv/y [1,22]. Dlung were ranging from 6.26 to 131.24 µSv/y with an average of 49.6±22.7 µSv/y, Dstomach were ranging from 0.45 to 9.45 µSv/y with an average of 3.6±1.6 µSv/y.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations